The National Health Services Commission Report Of 1944: Lessons from the Past for the Reconstruction of Social Services in a Post-Apartheid South Africa - Pillay, Yogan (PINS-Psychology in Society, 2026)
The National Health Services Commission Report (NHSCR) of 1944 has recently regained popularity and is frequently cited as the first such study that compiled a comprehensive report on the need for a national health service in South Africa. It has been described as an "enlightened" (De Beer, 1984) and "visionary" (Benatar, 1990) report. While these perceptions of the Commission's report may be contested, indeed it has been criticized by Marks (1987) and Packard (1989), the report (to the best of knowledge of the author) has not been evaluated in terms of its findings and recommendations with respect to social services. The issue that the Commission researched in the late 1930s and early 1940s is indeed relevant today - given the numerous calls for a unitary health service (e.g., Coovadia:1987); and Benatar:1990). The current literature on the transformation of South African health policy has tended to, with a few exceptions, ignore the issue of "social services" (this concept, popularized by the Organization of Appropriate Social Services of South Africa, is preferred and includes practices that are usually labelled mental health and social welfare). This paper attempts to revisit the NHSCR to evaluate its treatment of the role and location of social services in a national health service and to explore its possible lessons for current health and social service policy analysts.